2021
DOI: 10.1186/s12889-021-10788-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 crisis on work and private life, mental well-being and self-rated health in German and Swiss employees: a cross-sectional online survey

Abstract: Background The COVID-19 crisis has radically changed the way people live and work. While most studies have focused on prevailing negative consequences, potential positive shifts in everyday life have received less attention. Thus, we examined the actual and perceived overall impact of the COVID-19 crisis on work and private life, and the consequences for mental well-being (MWB), and self-rated health (SRH) in German and Swiss employees. Methods Cro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(102 citation statements)
references
References 55 publications
(39 reference statements)
4
94
0
4
Order By: Relevance
“…One of the largest sources of stress was an economic crisis due to prolonged lockdown, which increased concerns about future work-finding and financial stability [18,44]. Lee [45] showed that perceived employment and housing insecurity, deteriorating finances, and difficulties in paying for basic needs predicted life satisfaction, happiness, health selfesteem, mental health index, and mental stress among a large sample of European Union citizens.…”
Section: Introductionmentioning
confidence: 99%
“…One of the largest sources of stress was an economic crisis due to prolonged lockdown, which increased concerns about future work-finding and financial stability [18,44]. Lee [45] showed that perceived employment and housing insecurity, deteriorating finances, and difficulties in paying for basic needs predicted life satisfaction, happiness, health selfesteem, mental health index, and mental stress among a large sample of European Union citizens.…”
Section: Introductionmentioning
confidence: 99%
“…These impacts may disproportionately affect women (Arntz et al 2020). Evidence during the pandemic showed heterogeneous responses to WFHdecreased stress in some workers, increased stress in others (Aetna International 2020; Moretti et al 2020;Tu sl et al 2021;Weitzer et al 2021). A third health impact of WFH reported during the pandemic was weight gain (Aetna International 2020; Ekpanyaskul and Padungtod 2021); while this may relate to the general decrease in physical activity during the shutdown, it may also reflect the decline in commuting-associated physical activity (Abolanle et al 2020;Raza et al 2020).…”
Section: Infection-safe Buildings?mentioning
confidence: 99%
“…The consequence is a greater difficulty in concentrating on work tasks and even a lower productivity. Living alone has also been found to be a factor that exposes workers to a higher risk of psychological stress due to the greater feel of social isolation while working from home [38]. Of note, a study that evaluated the effects of working from home and working at the office among academic staff found greater parasympathetic activity, assessed by measuring heart rate variability, during working-from-home days [39].…”
Section: Working From Home and Psychological Stressmentioning
confidence: 99%
“…Once the negative lifestyle changes associated with working from home that are heightened with lockdown have been identified, it is fundamental to prevent these unhealthy behavior changes in workers transitioning to working from home. It is noteworthy that some positive effects of working from home have been reported, such as increased productivity [31], improved mental well-being due to increased leisure time [38], greater level of flexibility in time management [65] which enables workers to better control and schedule their daily activities, more relaxation [39,65], and the reduced need to commute [24,65]. Furthermore, it should also be taken into account that the impact on mental well-being may depend on the frequency of working from home [66] and on whether it is mandatory or optional.…”
Section: Future Perspectivesmentioning
confidence: 99%